2017
DOI: 10.1016/j.psyneuen.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the endocrine and autonomic stress systems does not impact the emotional stress experience after psychosocial stress

Abstract: Acute psychosocial stress activates the physiological and endocrine stress systems and increases the subjective emotional experience of stress. While considerable efforts have been made to link changes in the activity of the biological stress systems with changes in the subjective emotional experience of stress, results so far have been mixed, at best. To investigate this association in a study employing experimental manipulation, we pharmacologically suppressed both the autonomic and the endocrine stress resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 32 publications
(37 reference statements)
3
42
3
Order By: Relevance
“…In contrast, high trait anxiety was associated with lower neuroendocrine reactivity during psychosocial stress (Jezova, Makatsori, Duncko, Moncek, & Jakubek, 2004), with the result that higher anxiety was associated with an inability to respond to stress. A recent study, which aimed to explore the relationship between physiological and psychological stress responses, concluded that the emotional experience of stress and the physiological stress response were two dissociated systems (Ali et al, 2017). This result contrasts with what we found; it is likely that the level of anxiety was a more reliable psychological stress marker than the one used in the mentioned work, i.e., mood.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, high trait anxiety was associated with lower neuroendocrine reactivity during psychosocial stress (Jezova, Makatsori, Duncko, Moncek, & Jakubek, 2004), with the result that higher anxiety was associated with an inability to respond to stress. A recent study, which aimed to explore the relationship between physiological and psychological stress responses, concluded that the emotional experience of stress and the physiological stress response were two dissociated systems (Ali et al, 2017). This result contrasts with what we found; it is likely that the level of anxiety was a more reliable psychological stress marker than the one used in the mentioned work, i.e., mood.…”
Section: Discussioncontrasting
confidence: 99%
“…This issue was discussed by Het, Ramlow, and Wolf (2005) in the field of memory, in which, apparently, the timing of the treatment with respect to the course of the study (before learning vs. before retrieval) is important for evaluating the effect of stress on memory. Similarly, studies in which performance was evaluated when the cortisol concentration was elevated showed a negative correlation between behavioral performance and the cortisol response 2 Both cortisol and heart rate may have positive relationships with attentional performance (Table 1 C, E, c´); however, in the presence of anxiety, these relationships become negative ( , 2008). Furthermore, the effect of psychosocial stress on cognitive function was not present immediately after stress induction but gradually became evident (Plessow, Fischer, Kirschbaum, & Goschke, 2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As reported in our previous article, we did not observe differences between the groups in heart rate or cortisol, which is in line with the work of Ali et al . (2017), showing a dissociation of the emotional and affective experience of stress in a study with dexamethasone suppression 54 .…”
Section: Discussionmentioning
confidence: 97%
“…The initial saliva samples (saliva sample 1 (SS1), SS2, and SS3 in Figures 1a and 2b) were not included in the cortisol analyses since these samples are likely noisy measures, due to participants having just arrived in the lab and undergone EEG capping and gelling. Moreover, it is typical to include a waiting period after ACUTE STRESS AND REWARD 18 arriving in the lab prior to inducing stress (Ali, Nitschke, Cooperman, & Pruessner, 2017;Pruessner et al, 2008), and we were primarily interested in associations between baseline reward response and cortisol reactivity to stress. Therefore, the first sample following the stressor in the stress condition (SS4), and all subsequent saliva samples, were entered into the models for both groups.…”
Section: Discussionmentioning
confidence: 99%